MICROBIOLOGICAL PROFILES AND CLINICAL OUTCOMES OF BLOODSTREAM INFECTIONS IN GERIATRIC PATIENTS ADMITTED TO INTENSIVE CARE UNITS: A SINGLE-CENTER EXPERIENCE - Ari, Nuray; Sagmak Tartar, Ayse; Kayali, Sumeyra; Dayan, Serhat; Tanik Simsek, Bahar; Akbulut, Hatice Handan (Turkish Geriatrics Soc, 2025)
Introduction: Bloodstream infections are associated with high mortality in older adults due to immunosenescence and comorbidities. This study aimed to investigate pathogen distribution, antimicrobial resistance patterns, and predictors of early and late mortality in intensive care unit patients aged >= 65 years. Materials and Method: Between September 2022 and September 2024, blood culture results of intensive care unitpatients aged >= 65 years at F & imath;rat University Hospital were evaluated. The first clinically significant isolates were analyzed; identification and susceptibility were performed by automated systems and confirmed by conventional methods when necessary. Statistical analyses were conducted. Results: Among 469 patients, the most frequent pathogens were Klebsiella spp. (18.6%), Enterococcusspp. (16.8%), and Escherichia coli(12.6%). Extended-spectrum (3-lactamase positivitywas 77.0% in Klebsiella spp. 50.8% in Escherichia coli. In Klebsiella spp., imipenem and meropenem susceptibilities were 37.3% and 35.3%, respectively, and amikacin susceptibility was 84.9%. Acinetobacter spp. showed 94.7% susceptibility to colistin, while Staphylococcus aureus was 100% susceptible to vancomycin. Approximately 40-50% of Candida isolates demonstrated azole resistance. Secondary bloodstream infections occurred in 62.5%, with higher C-reactive protein levels (p=0.034). In multivariable analysis, only serum albumin was independently associated with early mortality. Conclusion: In geriatric intensive care unit patients, bloodstream infections were mostly secondary, predominantly caused by Klebsiellaspeciesand Escherichia coli.High Extended-spectrum (3-lactamase rates and marked carbapenem resistance complicatetreatment.Lowserum albumin independently predicted early mortality. Our findings highlight the need for close monitoring of infection burden and resistance patterns.
Keywords: Aged; Intensive Care Units; Sepsis; Bacteremia; Drug Resistance